Epistemologi Positivisme Dalam Filsafat - Sakti, Salwa Nurfauziyah; Nonci, Hajir; M, Marilang (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Speaking of the birth and development of philosophy, at the beginning of its birth it cannot be separated from the development of (science) knowledge that emerged during the Ancient civilization (Greek era). In 2000 BC, the Babylonians who lived in the Nile Valley (Egypt) and the Euphrates River had known weight measuring instruments, power number tables, multiplication tables using ten fingers. In this study, the author uses a qualitative descriptive approach with the main data source from library data. The results of the study show that the advantages of positivism are: Objectivity in positivism can be measured and tested empirically. Positivism recognizes the relativism of science. The implication is that it is more tolerant of differences in research results. Research using positivism can be applied to understand the past, present and predict the future. These advantages are related to the basic assumptions of positivism which aim to find general laws. Furthermore, these laws are able to describe the development of the history of the culture of a society. By using positivism, a researcher is only limited to the study of empirical socio-cultural phenomena. That means, they are only fixated on empirical reality and deny imaginary reality (discourse) when conducting research. Whereas a society has both realities in its daily life.